EFFICIENCY OF LOGISTIC SYSTEMS - S. M Salum (Наука и техника)
Main missions of production and distributive logistics are defined in the paper. The paper gives the concept of logistic distribution channel. The possibility of its selection is analyzed, and that is a significant reserve to improve efficiency of logistic processes.The paper considers efficiency of logistic and transport-technological systems on the basis of the relationship of aggregate gross revenue and aggregate costs of an enterprise.The paper cites a concept of economic criterion of efficiency describing the whole logistic chain, that is from the moment of primary raw materials output to consumption of products at all stages of production and transportation of primary raw materials, semi-finished and finished products.